A Prospective Comparative Study of Hemodynamic Response to Proseal Lma Insertion versus Endotracheal Intubation - Dr.Sudhanshu Sant; Dr.Archana Agarwal; Dr.Rohit Malhotra; Dr.Vikram Dalal (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Introduction: Airway management is a critical skill for anaesthesiologists. The airway can be maintained in a variety of ways, with endotracheal intubation being the gold standard. The use of laryngoscopy and intubation induces an increase in blood pressure and pulse rate. The hemodynamic response to laryngoscopy and tracheal intubation has been extensively documented, and several approaches have been attempted to mitigate it. This response is harmful in patients with a compromised cardiovascular system, especially if it is unregulated. Materials and Methods: A total of 100 patients were randomly selected from the list of elective surgical procedures under general anaesthesia. They were divided randomly by computer generated number method into two groups of 50 patients each. Group ET (n=50):Laryngoscopy and endotracheal intubation with appropriate sized cuffed PVC endotracheal tube was done. Group PLMA (n=50): PLMA size 3 or 4 as appropriate for the patient was inserted and cuff inflated with recommended volume of air. Results: The demographic profile of the patients in Group ETT and Group PLMA were comparable (P>0.05).There was no statistical difference in insertion attempts between endotracheal tube and PLMA. The difference in time required for endotracheal intubation and PLMA insertion was not statistically significant. There was a rise in heart rate and mean arterial pressure (MAP) seen after insertion of both devices, but there was comparatively higher rise seen with endotracheal tube than PLMA and it was statistically significant. Conclusion: From the findings of present study it is concluded that PLMA insertion causes significantly less and transient hemodynamic response in comparison to endotracheal intubation. Hence it could be useful in situations where minimal changes in hemodynamics are desirable. PLMA is also found to be equally safe compared to endotracheal tube, as not a single incidence of aspiration was noted with its use. We recommend routine use of PLMA in place of endotracheal intubation for elective surgical procedures lasting 1 to 2 hours.